THE CORRELATION BETWEEN STUDENT READING HABIT AND THEIR ABILITY OF WRITING NARRATIVE TEXT - Yana, Fitri (Faculty of Tarbiyah nad Teacher Training, 2024)
The objective of this study was to examine the reading behaviors of individuals learning the English language and see whether these behaviors are correlated with enhanced writing abilities. The study was conducted at 22 Tembung, MAS Al-Wasliyah. A total of 34 students were chosen randomly. In this research through random sampling technique. A questionnaire was used to measure how good the students’ reading habit and guided writing test to measure students’ ability of writing narrative text. After conducting the research, it was found that the average score of the students’ reading habit was 61.1%, that was in good level and the average score of the ability of writing narrative text was 72.4 that was categorized good as well. Moreover, the result of data analysis using SPSS shows that the correlation coefficient between the two variables (reading habit and writing ability) is 0.629, while the critical value for 34 students with 95% confidence is 0.339. Since the correlation coefficient obtained (0.629) is higher than the table value (0.339). It was concluded that there was a positive correlation between students‟ reading habit and their ability of writing narrative text.